Effects of six different microbial strains on polyphenol profiles, antioxidant activity, and bioaccessibility of blueberry pomace with solid-state fermentation - Tian, Zhu-Xi; Li, Yong-Fu; Long, Ming-Xiu; Liang, Qian; Chen, Xi; Huang, Dao-Mei; Ran, Yao-Qi (Frontiers in Nutrition, 2023)
To explore the effect of different microbial strains on blueberry pomace with solid-state fermentation (SSF), three fungi strains and three lactic acid bacteria (LAB) strains was utilized to investigate with respect to polyphenol profiles, antioxidant capacities and bioaccessibility. Different strains exhibited different capacities for metabolizing polyphenolic compounds in blueberry pomace. The contents of 10 phenolic acids and 6 flavonoids (except (+)-catechin) were increased in blueberry pomace fermented by Lactobacillus acidophilus (LA). A similar tendency was observed in blueberry pomace fermented by Aspergillus niger (AN) and Lactobacillus plantarum (LP), where the concentration of 8 phenolic acids and 5 flavonoids were enhanced, with the following exceptions: (+)-catechin, ferulic acid, vanillic acid, and quercitrin. Chlorogenic acid and quercetin were the maximum phenolic acids and flavonoids in blueberry pomace by SSF, upgraded by at highest 22.96 % and 20.16 %, respectively. Contrary to the growth of phenolic acids and flavonoids compounds, all individual anthocyanins showed a decreased trend. Only in the blueberry pomace fermented by AN did all anthocyanidins exhibit a rising trend. After SSF, 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-diphenylpicrylhydrazyl (DPPH), and ferric reducing antioxidant power (FRAP) radical scavenging abilities were increased by up to 33.56 %, 59.89 %, and 87.82 %, respectively. Moreover, simulated gastrointestinal digestion system revealed that SSF improved the bioaccessibility of polyphenolic compounds. Compared to other strains, LA, LP, and AN showed better excellent capacities for metabolizing polyphenolic compounds, which led to a greater increase of antioxidant activity and bioaccessibility in fermented blueberry pomace.